Rozwiąż i sprawdź następujące równania:
a)(x-1)²-x²=7
b)(x-1)(x+1)-x²=8x
c)3(x+2)²-3x²=18
d)2(x-4)²-2x²=16
e)5(x+7)²-5x²=105
f)6x²-6(x+3)(x-3)+3x=39
g)4x²-4(x+5)²=20
h)(2x-7)(2x+7)+5x=4x²+11
i)(2x+3)²-4(x²+8)=13
j)(3x-2)²-3(3x²-5)=-5



Z góry dzięki za rozwiązanie ;)

2

Odpowiedzi

2009-11-22T16:39:13+01:00
A)(x-1)²-x²=7
x²-2x+1-x²=7
-2x=7-1
-2x=6 /*(-1)
2x=-6
x=-3

b)(x-1)(x+1)-x²=8x
x²-1-x²=8x
8x=-1
x=-1/8

c)3(x+2)²-3x²=18
3(x²+4x+4)-3x²=18
3x²+12x+12-3x²=18
12x=18-12
12x=6
x=1/2

d)2(x-4)²-2x²=16
2(x²-8x+16)-2x²=16
2x²-16x+32-2x²=16
-16x=16-32
-16x=-16 /*(-1)
16x=16
x=1

e)5(x+7)²-5x²=105
5(x²+14x+49)-5x²=105
5x²+70x+245-5x²=105
70x=105-245
70x=- 140
x=-2

f)6x²-6(x+3)(x-3)+3x=39
6x²-6(x²-9)+3x=39
6x²-6x²+54+3x=39
3x=39-54
3x=-15
x=-5

g)4x²-4(x+5)²=20
4x²-4(x²+10x+25)=20
4x²-4x²-40x-100=20
-40x=20+100
-40x=120 /*(-1)
40x=-120
x=-3

h)(2x-7)(2x+7)+5x=4x²+11
4x²-49+5x=4x²+11
4x²+5x-4x²=11+49
5x=60
x=12

i)(2x+3)²-4(x²+8)=13
4x²+12x+9-4x²-32=13
12x=13+23
12x=36
x=3


j)(3x-2)²-3(3x²-5)=-5
9x²-12x+4-9x²+15=-5
-12x=-5-19
-12x=-24 /*(-1)
12x=24
x=2
2009-11-22T16:40:27+01:00
A)(x-1)²-x²=7
x²+1-2x-x²=7
-2x=6
x=-3
b)(x-1)(x+1)-x²=8x
x²-1-x²=8x
-1=8x
x=-1/8
c)3(x+2)²-3x²=18
3(x²+4+4x)-3x²=18
3x²+12+12x-3x²=18
12x=6
x=1/2
d)2(x-4)²-2x²=16
2(x²+16-8x)-2x²=16
2x²+32-16x-2x²=16
-16x=-16
x=1
e)5(x+7)²-5x²=105
5(x²+49+14x)-5x²=105
245+70x=105
70x=-140
x=-2
f)6x²-6(x+3)(x-3)+3x=39
6x²-6x²+54+3x=39
3x=-15
x=-5
g)4x²-4(x+5)²=20
4x²-4x²-100-40x=20
-40x=120
x=-3
h)(2x-7)(2x+7)+5x=4x²+11
4x²-49+5x=4x²+11
5x=60
x=12
i)(2x+3)²-4(x²+8)=13
4x²+9+12x-4x²-32=13
12x-23=13
12x=36
x=3
j)(3x-2)²-3(3x²-5)=-5
9x²+4-12x-9x²-15=-5
-12x-11=-5
-12x=6
x=-1/2